Re-reading Alencar's Iracema through Saer's Lens - Felicia Trievel (Vernacular: New Connections in Language, Literature, & Culture, 2021)
Abstract: The topic of European colonization is one that is discussed frequently throughout Latin American literature in a variety of different manners. Two books that discuss the colonization of different countries in extremely different ways are Iracema (1865) by José de Alencar and El entenado (1983) by Juan José Saer. The former examines the colonization of Brazil by Portuguese colonists, taking away much of the culture of the indigenous people previously inhabiting Brazil. El entenado examines the colonization of Argentina by the Spaniards. When one reads these two novels it is impossible not to compare the two due to the similarity in content and the differences in style, but little literary analysis has been done making such a comparison. Such a comparison is necessary because Saer as an author provides a stark contrast to Alencar in his beliefs on ideology and nationalism in literature. When both authors are considered together, the reader is able to develop a more complete and critical understanding of the “Indian novel.” In this essay, I make such a comparison, drawing on the different features of the text such as the type of language used, narrative techniques and styles, symbolism, and ideology of the author to discuss the different representations of indigenous people. Throughout I will also seek to cite the validity of the representations based on historical events as well as any potential bias on the part of the author in their retelling of history.
Keywords: Iracema; El entenado; Juan José Saer; Alencar; indigenous novels; Latin American; Literature; Colonization